Konsumen Sayur Berbasis Food Safety di Kota Padang - Dr. Skunda Diliarosta, (SEMESTA: Journal of Science Education and Teaching, 2019)
The case of food poisoning in Padang city back then in 2017 – 2018 indicated that various regulations such as government laws and regulations made by the government were still not able to promote cautiousness among consumers in choosing groceries. This also indicated that those law and regulations failed to stop food manufacturer or producer from using harmful substances in food management and processing. Numerous cases of food poisoning were reported on television broadcast or in newspaper almost in daily basis. Based on these facts, we would like to conduct a study to figure out the habit of consumers in buying vegetables mainly in terms of food security (or food safety). This study also aimed to determine the level of knowledge and understanding of people in choosing vegetables that have a good level of food safety. This descriptive-analysis quantitative study focused on consumer awareness of food choices consumed based on food safety, which is measured from the change of community habits in the city of Padang. The subjects of this study were consumers who always shop in the Inpres market, the Alai market and the Lubuk Buaya market. This study is conducted in two stages. In the first stage, we distributed questionnaires that contain public knowledge about food safety to see consumers’ habit in choosing vegetables. Our findings indicated that only 3.2% of consumers understand that the decision to buy vegetables is associated with food security. As much as 54.03% of our subjects do not really care whether the vegetables consumed contain pesticides or not. We provided counselling, guidance on how to select good and healthy vegetables aided by organic vegetable brochures and a pin to mark our consumers. In the second phase, we provided counselling, guidance on how to choose vegetables that are safe to consume and the negative impacts from consuming vegetables that contain residual chemicals from fertilizers and pesticides. The results showed changes in consumers’ behaviour in choosing vegetables that have food safety. Through this study, we expect that the numbers of consumer who aware of the importance of having good level of food safety will increase and therefore will I turn reduce the number of food poisoning cases in Indonesian.